DYNAMICS OF CIVIL LAW IN THE ENFORCEMENT OF UNWRITTEN AGREEMENTS IN BUSINESS ACTIVITIES - Ratnagung, Catur Galuh (Yayasan Education and Social Center, 2024)
This research analyzes the dynamics of civil law related to the enforcement of unwritten agreements in the context of business activities in Indonesia. Through a qualitative approach, this research highlights the gap between legal recognition of unwritten agreements and practical challenges in enforcement. The findings show that the lack of written evidence is a major obstacle in litigation, increasing legal uncertainty and risk for business actors. The role of good faith on the part of the parties is also identified as a key factor in enforcing the agreement. However, awareness of the importance of good faith still needs to be increased among business people and legal practitioners. In addition, this research emphasizes the need for broader legal reform to increase the effectiveness of enforcing unwritten agreements, including the creation of clearer regulations and more effective enforcement mechanisms. Thus, this research contributes to further understanding of the complexity of enforcing unwritten agreements in business practices in Indonesia